TECHNOLOGY AND THE TRANSFORMATION OF EDUCATIONAL PRACTICES: A FUTURE PERSPECTIVE - Gowher Hassan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Educational technology is undergoing a transformative evolution, bringing forth a convergence of digital tools, platforms, and methodologies to augment the learning journey. The proliferation of Learning Management Systems (LMS) and collaborative tools has ushered in an era of online learning, amplified by global shifts like the COVID-19 pandemic. These virtual platforms are redefining the boundaries of teaching, enabling a connection beyond physical spaces. Simultaneously, advancements in artificial intelligence and data analytics are reshaping personalized learning by discerning individual learner needs and facilitating real-time feedback. This evolving landscape is further enriched by emergent technologies like Artificial Intelligence (AI), Virtual Reality (VR), and Augmented Reality (AR). These innovations offer immersive, tailored experiences, reimagining traditional pedagogies. AI tailors education to individual needs, VR offers experiential realms previously unattainable, and AR provides an enriched overlay of information on the real world, revolutionising engagement. However, with these strides comes a responsibility to address underlying challenges: ensuring privacy, bridging the digital divide, and addressing potential biases in educational algorithms. The focus on accessibility and inclusivity is paramount, and technology plays a pivotal role in democratizing access to quality education. This synthesis underscores the imperative of interweaving technological advancements with core educational values, ensuring that the integration is both meaningful and equitable.